Sex-Related Hemispheric Lateralization of Amygdala Function in Emotionally Influenced Memory: An fMRI Investigation - Cahill, Larry (Cold Spring Harbor Laboratory Press, 2004)
The amygdala appears necessary for enhanced long-term memory associated with emotionally arousing events. Recent brain imaging investigations support this view and indicate a sex-related hemispheric lateralization exists in the amygdala relationship to memory for emotional material. This study confirms and further explores this finding. Healthy men and women underwent functional Magnetic Resonance Imaging (fMRI) while viewing a series of standardized slides that were rated by the subjects as ranging from emotionally neutral to highly arousing. Two weeks later, memory for the slides was assessed in an incidental recognition test. The results demonstrate a significantly stronger relationship in men than in women between activity of the right hemisphere amygdala and memory for those slides judged as arousing, and a significantly stronger relationship in women than in men between activity of the left hemisphere amygdala and memory for arousing slides. An ANOVA confirmed a significant interaction between sex and hemisphere regarding amygdala function in memory. These results provide the strongest evidence to date of a sex-related hemispheric lateralization of amygdala function in memory for emotional material. Furthermore, they underscore the view that investigations of neural mechanisms underlying emotionally influenced memory must anticipate, and begin to account for, the apparently substantial influence of sex.